Biosimilars in Dermatology: A Promising Solution to The High Cost of Biologic Therapy: Pharmaceutical Science-Dermatology - S. Hussein, Ramadan; Dayel, Salman Bin (International Journal of Life Science and Pharma Research, 2023)
Biologic therapy has revolutionized the management of many chronic illnesses, including dermatological conditions.However, their high cost remains a significant barrier to global access for patients and healthcare systems. Biosimilars are highlysimilar versions of reference biologics that have the potential to provide comparable efficacy and safety at a lower cost. Theavailability of biosimilars in dermatology is increasing, and their impact on patient outcomes and healthcare systems is beingevaluated. Despite numerous reviews published on biosimilars, the literature needs a comprehensive and critical analysis of theiruse in dermatology. This review aims to address this lacuna by providing an up-to-date overview of the available evidence onbiosimilars in dermatology. This review evaluates biosimilars’ efficacy, safety, and cost-effectiveness in dermatological conditions,including psoriasis, atopic dermatitis, and psoriatic arthritis. Our objective is to provide a comprehensive and critical analysis ofthe current evidence, identify knowledge gaps, and discuss biosimilars’ potential impact on patient outcomes and healthcaresystems. We systematically reviewed the literature using several databases, including Medline, PubMed, Embase, and Scopus, toachieve our aim and objective. We included randomized controlled trials, systematic reviews, and observational studies thatevaluated the use of biosimilars in dermatology. Our review found that biosimilars are a promising solution to the high cost ofbiologic therapy in dermatology. Biosimilars have demonstrated comparable efficacy and safety to their reference biologics inseveral dermatological conditions. Furthermore, the cost-effectiveness of biosimilars is a significant advantage, allowing greateraccess to biologic therapy for patients and reducing the financial burden on healthcare systems.